Ideology in Spanish Press: Discursive Treatment of Rare Disease Ataxia - Ridao Rodrigo, Susana (Estudios sobre el Mensaje Periodístico, 2012)
The press is a suitable means to analyze the underlying ideology in the treatment of certain social aspects of communication. Existing publications in this area have focused, primarily, on researching in immigration; in our opinion, this situation is, in some way, extrapolated to treatment of diseases with low prevalence. Thus, this paper conducted a study of the discursive representation of ataxia, a rare disease, in the Spanish press; more specifically, we analyze the newspapers El País, El Mundo and ABC, using quantitative and qualitative variables. As our foremost conclusion, we would like to emphasize that, as expected, these news deal with health issues, but only the 36.08% of the corpus obtained approach the disease of ataxia as a priority topic.